DESAIN EKSPERIMENTAL FAKTORIAL UNTUK PENENTUAN FAKTOR PALING BERPENGARUH PADA PROSES PULPING ORGANOSOLV BERBAHAN BAKU LIMBAH DAUN NANAS - Rayhan, Glenn Mochamad; Fachrina, Salsabila; Amalia, Rizka (Vocational School Diponegoro University, 2020)
Paper production has been identified with industries that destroy forests (deforestation). Utilizing alternative wood substitute raw materials, such as pineapple leaves can be one solution to the problem. Pineapple plants can produce more than 70 leaves with cellulose content in the leaves which reaches 69.5-71.5%, so it has the potential to be used as raw material for paper. The organosolv process was chosen as a pulp manufacturing process because it produces high purity in the byproducts (lignin and hemicellulose), high pulp yield, easy recovery of black liquor and no sulfur element, making it safer for the environment. This study aims to determine the most influential factors in the organosolv pulping process with a factorial experimental design method 23. Variables used include solvent types (ethanol and acetic acid), pulp cooking time (60 minutes and 110 minutes) and types of leaf dryness (wet leaves) and dried leaves). From the results of the analysis, the most influential factor in the organosolv pulping process is the type of solvent (ethanol). Optimal operating conditions were obtained for solvent ethanol, cooking time of 60 minutes with wet leaves, where cellulose content was 96.31% and lignin content decreased by 17.80% in dry pulp.